Iterative application method for solving system modified korteweg-de vries equations - Y.Ali, Zeiad; ., Allawee (International Journal of Engineering and Technology, 2019)
In this paper we use a new iterative method (NIM) to solution the floating wave the new modified Korteweg-de Vries equations. We have shown that a more accurate NIM solution with modified Korteweg-de Vries equations is very efficient, convenient and completely accurate for nonlinear equations systems. The NIM solution is expected to find a wide-ranging application in engineering or physics. The results also show that the NIM solution is more reliable and easy to compute and compute speed than HPM and Heâ€™s Method (NIM) is introduced to overcome the difficulty arising in calculating Adomian polynomials.Â Â